Study on Public Satisfaction With Using Public Facilities (Kebun Bunga Stadium Complex, Medan City) - Adiniati, Fiska Mira; Hasibuan , Gina Cynthia Raphita; Anas , Muhammad Ridwan; Bangun , Emma Patricia; Mardianta , Anthoni Veery (Universitas Ibn Khaldun Bogor, 2025)
Rapid urban growth demands the availability of comfortable, safe, and functional public open spaces as part of the quality of life for urban communities. The Kebun Bunga Stadium Complex in Medan is one such public space used for various social, sports, and recreational activities. This study uses the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods to evaluate the level of public satisfaction with the utilization of public facilities at the Kebun Bunga Stadium Complex. Primary data was collected through the distribution of questionnaires to 130 randomly selected respondents. The results of the importance analysis (MIS) identified the highest importance values, reflecting the most dominant customer expectations or perceptions, in terms of comfort with very high importance (up to 4.64), visitor activities receiving significant attention (up to 4.61), and sociability, which respondents rated as very important (up to 4.59). This confirms that comfort and visitor activities are the primary focus areas that need to be addressed and improved to meet visitor expectations. The analysis results showed a CSI value of 76.89%, which falls into the “satisfied” category. However, based on the IPA mapping, several important attributes were identified, such as inadequate gym facilities, cleanliness and comfort, as well as access to public transportation and dedicated pathways for people with disabilities, which are not yet adequate. These are the main focus areas because they have a high level of importance but low performance. The results of this study serve as the basis for recommendations for the government to improve the management and service of public facilities, thereby providing optimal comfort and satisfaction for the community.